2022
DOI: 10.1021/acs.analchem.2c03338
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Discrimination of Single Nucleotide Polymorphisms by Quantification of CRISPR-Cas Catalytic Efficiency

Abstract: The specificity of CRISPR-Cas12 assays is attractive for the detection of single nucleotide polymorphisms (SNPs) implicated in, e.g., cancer and SARS-CoV-2 variants. Such assays often employ endpoint measurements of SNP or wild type (WT) activated Cas12 trans-cleavage activity; however, the fundamental kinetic effects of SNP versus WT activation remain unknown. We here show that endpoint-based assays are limited by arbitrary experimental choices (like used reporter concentration and assay duration) and work be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Some past studies have incorrectly reported that such a PAM is required for Cas12a activation for dsDNA targets, 38,39 but subsequent work has shown that PAM makes only a limited contribution to DNA unwinding. 18,40 Experimental Evaluation of gRNA and Reporter Selection. Example kinetic measurements are listed in Figure 1c.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Some past studies have incorrectly reported that such a PAM is required for Cas12a activation for dsDNA targets, 38,39 but subsequent work has shown that PAM makes only a limited contribution to DNA unwinding. 18,40 Experimental Evaluation of gRNA and Reporter Selection. Example kinetic measurements are listed in Figure 1c.…”
Section: ■ Resultsmentioning
confidence: 99%
“…A DNA strand modified with 6-carboxyfluorescein (6-FAM) at the 5′ end and black hole quencher 1 (BHQ1) at the 3′ end serves as the reporter of Cas12a. When the reporter is cut off via Cas12a activated by the RPA amplicon, the distance between 6-FAM and BHQ1 increases and the fluorescence from 6-FAM could be recovered. , The assay based on primer extension and CRISPR/Cas ensures reliable discrimination of single-nucleotide mutations in the fungal genome. Due to the high amplification efficiency of RPA, iARMS yields a high sensitivity for detecting fungi, and the detection processes could proceed at a constant temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Although targeting mutations located in the PAM-proximal region has improved the specificity of CRISPR-Cas12a for the differentiation of SARS-CoV-2 and its variants, the ability of CRISPR-Cas12a to differentiate single nucleotide polymorphisms (SNPs) still needs to be further improved. Single-nucleotide mutation does not always lead to a decrease in the signal at a particular time point [ 141 ]. In a test covering all 60 possible mutations within a 20 nt protospacer, the mutant can even have a higher signal than the wild-type at one time point [ 141 ].…”
Section: Crispr-cas12-based Methods For the Detection Of Variantsmentioning
confidence: 99%
“…Single-nucleotide mutation does not always lead to a decrease in the signal at a particular time point [ 141 ]. In a test covering all 60 possible mutations within a 20 nt protospacer, the mutant can even have a higher signal than the wild-type at one time point [ 141 ]. An alternative strategy was to use the kinetics parameters for variant discrimination, because all these variants exhibited a lower catalytic efficiency ( k cat /K M ) than that of the wild-type [ 141 ].…”
Section: Crispr-cas12-based Methods For the Detection Of Variantsmentioning
confidence: 99%